Improvement of performance unitary refrigerant systems for hot climate in Baghdad city - Y. Abdul-Kareem, Mazin; Abdul muttaleb Sadeq, Luay; Saad Ismail, Hisham (International Journal of Engineering and Technology, 2019)
This research aims to improve work unitary refrigeration systems and decreasing of electric energy consumption in Baghdad city. The work presents study effect of adding the simple evaporative cooling system to the outdoor unit of refrigeration system under various climate conditions, the effect on cooling capacity and the electric current consumption at system. The outdoor air at condenser enter was cooled by the simple system and its effectiveness (43% to 50.4%). The results reveal that dry bulb temperature of air reduces (16% to 25.3%) at enter to the condenser and the rejected heat increases (empirical 43% to 59.8%) under various operating conditions. Indoor air conditions, dry bulb temperature of air at the inlet of evapo-rator reduces (41.3% to 44.4%) and the variation in refrigeration gas temperature in the evaporator is (46.6% to56%). This will increase cooling capacity in evaporator which increased (53.6% to 62%) at work presented conditions. The noticeable that using simple evaporative cooling system reduces the electrical current consumption by (22.5% to 25%) which reduce operating costs. Nomenclature:T: Temperature(ºC).Tref: Refrigeration gas temperature(ºC).RH: Relative humidity of air (%).h: Specific enthalpy of air (kJ/kg).I: Electric current (A).Qrej: Rejected heat of condenser (kW).Qc.c.: Cooling Capacity (kW).